AN ELECTRON MICROSCOPIC STUDY OF THE DEVELOPMENT OF THE CLEAVAGE FURROW IN MAMMALIAN CELLS - Buck, Robert C. (The Rockefeller University Press, 1962)
The process of cytoplasmic cleavage has been studied in thin sections of rat erythroblasts and the cells of mouse leukemia and Walker 256 carcinoma of the rat. The development of the cleavage furrow begins in relation to the mid-body, which, earlier, appears on the equatorial plane in association with the continuous fibers of the spindle. The earliest evidence of a cleavage furrow is the presence of a vesicle or vesicles close to the mid-body. Subsequently, many smaller vesicles are seen in the equatorial plane. The cleavage furrow probably develops by the fusion of these vesicles so that a new plasma membrane is formed between the daughter cells, and extends from the telophase intercellular bridge to the cell margin. During the stage of formation of the vesicles, cisternae, believed to be part of the endoplasmic reticulum, assume an intimate relationship with the cleavage plane, and they may perhaps be involved in the formation of the vesicles.